Corrosion behaviour of ZrO2-TiO2 nano composite coating on stainless steel under simulated marine environment. (2020) - Mohan, Sreejith; Nair, Sivakumar S.; Ajay, A.V.; Senthil Saravanan, M.S.; Vishnu, B.R.; Sivapirakasam, S.P.; Surianarayanan, M.
Abstract: Nano structured ZrO2 -TiO2 film coating was realized on AISI 304 stainless steel using the sol-gel dip coating technique. The effect of coating on the corrosion resistance of steel was investigated in simulated marine water using potentiodynamic polarization measurement. The effect of coating process parameters on the corrosion rate was systematically investigated using the Taguchi methodology of DoE. The results reveal an appreciable enhancement of as much as 88.21% in corrosion resistance of stainless steel with the additional coating. The morphology, thickness and micro hardness of the coating were found to influence the corrosion resistance.